TI_GERICHTE 15.2007.30 vom 9. August 2007 , Amministrazione coatta di bene immobile. Compiti dell'amministrazione - TI Tribunale d'appello (2007)
Amministrazione coatta di bene immobile. Compiti dell'amministrazione